2015
DOI: 10.1002/lary.25734
|View full text |Cite
|
Sign up to set email alerts
|

Assessing delays in laryngeal cancer treatment

Abstract: 4. Laryngoscope, 126:1612-1615, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
(26 reference statements)
1
35
1
Order By: Relevance
“…97 Another study found that patients routinely delay medical evaluation of hoarseness symptoms for >100 days. 98 Prompt referral by primary care physicians could improve outcomes and QOL.…”
Section: Supporting Textmentioning
confidence: 99%
“…97 Another study found that patients routinely delay medical evaluation of hoarseness symptoms for >100 days. 98 Prompt referral by primary care physicians could improve outcomes and QOL.…”
Section: Supporting Textmentioning
confidence: 99%
“…In addition, smokers with lower risk of relapse and death in a 5-year period when compared with non-smokers, as we showed (only 4 in this study), could be explained by genetic and molecular alterations considered as a distinct pathological entity and leading to poor prognosis; thus, this fact needs more investigation. 13 14 Complementary, in the literature, more relapses are observed in smokers as genetic alterations remains in patients, even after quitting the habit, and the presence of concept of field cancerization in these subjects is very important . 15 16 Another factor is that most of the smokers do not quit the habit, which increases the rate of second primaries and decreases the OS.…”
Section: Discussionmentioning
confidence: 93%
“…The former can be separated into patient-related delays-delays from the onset of symptoms to presentation to a physician-and professional delays-delays from presentation to diagnosis and treatment initiation. 14,15 Much of the work on delays during treatment have focused on interruptions during radiation therapy (RT), which are hypothesized to allow for proliferation of aggressive tumor clones. [16][17][18] Treatment times have been a subject of research in head and neck cancer (HNC), with a focus on the total length of treatment.…”
mentioning
confidence: 99%